1980
DOI: 10.1017/s0010417500009282
|View full text |Cite
|
Sign up to set email alerts
|

The Uses of Comparative History in Macrosocial Inquiry

Abstract: Comparative history is not new. As long as people have investigated social life, there has been recurrent fascination with juxtaposing historical patterns from two or more times or places. Part of the appeal comes from the general usefulness of looking at historical trajectories in order to study social change. Indeed, practitioners of comparative history from Alexis de Tocqueville and Max Weber to Marc Bloch, Reinhard Bendix, and Barrington Moore, Jr. have typically been concerned with understanding societal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
297
0
30

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 704 publications
(327 citation statements)
references
References 13 publications
0
297
0
30
Order By: Relevance
“…Skocpol and Somers 1980). It may be suggested that there are useful parallels to be drawn between historical case comparisons and the 'gender systems' approach to the study of gender relations (Crompton 1999a: 203ff).…”
Section: Methodology Data Collection and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Skocpol and Somers 1980). It may be suggested that there are useful parallels to be drawn between historical case comparisons and the 'gender systems' approach to the study of gender relations (Crompton 1999a: 203ff).…”
Section: Methodology Data Collection and Analysismentioning
confidence: 99%
“…Kohn 1987). Other researchers have focused more on the difference between cases, or the contrast of contexts (Skocpol and Somers 1980), in order to understand divergent historical developments. Besides the work of gender systems researchers (see above) one might also mention here the debates deriving from Esping-Andersen's Three Worlds of Welfare Capitalism (1990).…”
Section: Methodology Data Collection and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Tilly (1984) emphasized the operationalization of quantitative sociological research and analytic methods for historical use; he engaged in important comparative studies, but he also warned against overreliance on a comparative strategy. Skocpol (1979;Skocpol and Somers 1980) placed a distinctive stress on comparison. While Skocpol's (1979) cases happened to be historical, her analytic method was less distinctively so.…”
Section: Rampant Inductivism In Historical Sociology?mentioning
confidence: 99%
“…The cases for the analysis of social democratic development were selected according to the comparative method of "contrasted contexts" (p. 6), as introduced by the historians Skocpol and Somers (1980). This already indicates the editors' and authors' orientation towards an analysis of historical processes.…”
mentioning
confidence: 99%